Education and citizenship in diverse societies - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 2001)
The question of the state's role in the control of sponsorship of education is addressed in the light of liberal political principles designed to keep peace and enforce toleration in culturally diverse societies. Some contemporary, self-described liberal philosophers argue for a much more substantial educational role for the state than liberal principles will really allow. Brian Barry's argument for that role assumes that the state can prescribe answers to controversial questions regarding the truth and the good life in which a truly liberal state would take no interest. Stephen Macedo is more accommodating to religious diversity than Barry, but his argument fails because of his rashly optimistic view of the state's effectiveness in promoting civic virtue and the possibility of reconciling that role with fundamental liberal values. Liberal regimes do not depend on civic education, even under conditions of diversity. Their life-blood is toleration and dissent rather than the widespread diffusion of civic virtue.